PENGEMBANGAN RPP MODEL TGT BERBASIS PERMAINAN JAMURAN MATERI KALOR DAN PERPINDAHAN KELAS VII - Tita Febrianika Ashfina; Nindha Ayu Berlianti; Nur Kuswanti (Discovery, 2022)
Abstract: This development research is entitled Development of a Learning Implementation Plan (RPP) for the TGT Type (Team Games Tournament) Cooperative Model based on the traditional game of Mushroom on Heat and Displacement material. The background of this development research is the problem of the learning process using scientific methods but not yet in accordance with the steps and implementation. This study aims to describe the steps for developing a Learning Implementation Plan (RPP) for the Cooperative Type TGT model based on the Mushroom game. As well as describe the quality of the results of the development of the Learning Implementation Plan (RPP). The quality of the development results is determined based on the criteria of validity. The material used in the development is the material of Heat and displacement class VII.This research is research and development. The Learning Implementation Plan (RPP) development model was adapted from the Ploomp model development model which consisted of preliminary investigation, design, realization, evaluation and revision, and implementation. The research instrument used was a validation sheet for the product developed in the form of a LearningImplementation Plan (RPP). Validity data analysis was carried out by converting quantitative data in the form of assessment scores into qualitative data.This development research resulted in a Learning Implementation Plan (RPP), Student Worksheet (LKPD) and Assessment Instruments on Heat and Displacement material. Each Aspect of the Learning Implementation Plan (RPP) meets valid quality. Keywords: Development, RPP, TGT (Team Games Tournament), Heat a Displacemen